KEAMANAN AUTHENTIKASI HOTSPOT MENGGUNAKAN CAPTCHA - Prasetyo, Kiki Pradikta; Widiyanti, Rahayu; Setyowibowo, Sigit (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2015)
Hotspot networking SMKMuhammadiyah2Malang do not have a good security system that can be used by unauthorized users. With the issue of the security system research and design that has a hotspot networks security level better than before. The purpose of this study is to secure hotspot network of ilegal users by adding a captcha in the authentication process using MikroTik hotspot. Data collection methods used to analyze the data and make the information that will be used to determine the problems faced. System development method using the waterfall method. The use of captcha on the authentication process hotspot login page in SMK Muhammadiyah 2 Malang using Mikrotik has not been able to provide evidence of the power system network security hotspot. This is evidenced by the test using a brute force attack techniques. The testing process using the same time frame with the type of passwords that are very weak and not obtained differences of the results achieved. Hotpsot proxy authentication security system based captive portal using only user and password as the authentication process already has a good level of security even without using captcha. Keyword:Networking Security, authentication, hotspot, captcha.